(untitled) (Progressive Agriculture, 2014)
The economy of Bangladesh is mainly dependent on agriculture; agricultural development in the country to a great extent is dependent on the contribution of quality agricultural graduates. Agricultural universities on Bangladesh are responsible for producing competent agricultural graduates to cater the needs of the farmers and help them to solve the problems towards higher agricultural production. The existing course curricula and syllabi of the agricultural universities, in many cases, cannot meet the demand of the farmers, especially in the case of crisis situation like salinity, drought, disaster, climatic change etc. In the present article the challenges in higher agricultural education in Bangladesh has been critically reviewed. The present status of higher agricultural education, and challenges in higher agricultural education on different aspects have been discussed. The challenges need to be addressed if the quality agricultural graduates have to be produced by the agricultural universities.